2021
DOI: 10.32382/mf.v17i2.2209
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Metode Analisis Kuersetin dalam Ekstrak Etanol Buah Leunca (Solanum nigrum L.) Menggunakan Kromatografi Cair Kinerja Tinggi

Abstract: Buah leunca (Solanum nigrum L.) mengandung senyawa flavonoid yang berkhasiat sebagai antioksidan. Flavonoid di dalam buah leunca sebagian besar berupa kuersetin dan turunan glikosidanya. Kuersetin bersifat polar dan dapat dianalisis menggunakan kromatografi cair kinerja tinggi (KCKT). Tujuan penelitian ini adalah mengembangkan metode penetapan kadar kuersetin menggunakan KCKT dan mengaplikasikan metode pada ekstrak etanol buah leunca. Buah leunca diekstraksi dengan pelarut etanol 96% secara metode maserasi dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The difference in IC50 levels from white galangal extract and it can be concluded that the HPLC method is more effective than the spectrophotometer method (Cahyono et al, 2021). The HPLC method can be applied in testing the quercetin content which has been validated method with a value of 0.0086% and can be applied in determining the quercetin content in the ethanol extract of Leunca fruit Husnia and Budiarti, 2021).…”
Section: High Performance Liquid Chromatographymentioning
confidence: 99%
“…The difference in IC50 levels from white galangal extract and it can be concluded that the HPLC method is more effective than the spectrophotometer method (Cahyono et al, 2021). The HPLC method can be applied in testing the quercetin content which has been validated method with a value of 0.0086% and can be applied in determining the quercetin content in the ethanol extract of Leunca fruit Husnia and Budiarti, 2021).…”
Section: High Performance Liquid Chromatographymentioning
confidence: 99%